ANALISIS KEJADIAN ANEMIA PADA REMAJA PUTRI DITINJAU DARI PENGETAHUAN DAN RIWAYAT MENSTRUASI DI WILAYAH KERJA PUSKESMAS STUNGKIT KECAMATAN WAMPU TAHUN 2022 - Nilawati Nilawati; Ninsah Mandala Putri Sembiring (Pusat riset dan Inovasi Nasional, 2022)
Adolescence between the ages of 10-19 years, is a transitional period experienced by a person with physical and psychological changes. One of the health problems that occur in adolescents is anemia. This study aims to determine the incidence of anemia, the relationship between knowledge and menstrual history in the Working Area of ​​the Stungkit Health Center, Wampu District, in 2022. This type of research is an analytical survey with a cross sectional method approach. The number of samples used was 40 people. The data analysis technique uses the Chi Square test. the results obtained from 40 respondents, obtained a value of p = 0.001 (P> 0.05) this means that there is a relationship between knowledge and the incidence of anemia in young women. p value = 0.000 (P > 0.05) this means that there is a relationship between menstrual history and the incidence of anemia in young women.